Method for improving iron removal efficiency by using fluorine-containing waste sulfuric acid to perform high-pressure acid pickling on quartz sand

By using fluorine-containing waste sulfuric acid and high-pressure pickling solution to high-pressure pickling, the high cost and environmental pollution problems caused by high-temperature roasting in the prior art are solved, and the effect of efficiently removing impurities inside quartz sand is achieved.

CN119774624AActive Publication Date: 2025-04-08JIANGXI JIANJI HIGH TECH SILICON MATERIAL CO LTD +1

Patent Information

Application Number
CN202411980303.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The prior art requires high-temperature roasting when removing impurities inside quartz sand, resulting in high costs and large fossil energy consumption. At the same time, fluorine-containing waste sulfuric acid is difficult to deal with and easily lead to environmental pollution.

Method used

The quartz sand is subjected to high-pressure pickling solution (containing oxalic acid, phosphoric acid, hydrogen peroxide, N,N-dimethylformamide and surfactant) and reacts with the quartz sand with fluorine ions to penetrate deep into the cracks of the quartz sand and remove internal impurities.

Benefits of technology

It improves the iron removal efficiency of quartz sand, reduces the cost of removing impurities, avoids energy consumption of high-temperature roasting, and effectively utilizes fluorine-containing waste sulfuric acid, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for improving iron removal efficiency by using fluorine-containing waste sulfuric acid for high-pressure acid pickling of quartz sand, and relates to the technical field of purification of quartz sand. The pickling method comprises the following steps: mixing fluorine-containing waste sulfuric acid, oxalic acid, phosphoric acid, a hydrogen peroxide solution, N, N-dimethylformamide, a surfactant and water to obtain a composite high-pressure pickling solution; performing high-pressure pickling on the quartz sand by adopting a composite high-pressure pickling solution; and washing the quartz sand after the high-pressure pickling is completed to obtain a quartz sand product. The fluorine-containing waste sulfuric acid is adopted as a main component to prepare the composite high-pressure pickling solution, and the quartz sand is subjected to pickling by using high-pressure pickling equipment, so that the problems of resource waste and environmental pollution caused by difficult recycling of the fluorine-containing waste sulfuric acid are solved, and the problem that impurities in the quartz sand are difficult to remove is also solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz sand purification, in particular to a method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid. Background Art

[0002] Quartz sand is an important industrial mineral raw material, mainly made of quartz stone through crushing, screening and other processes. The main component is silicon dioxide, which is widely found in igneous rocks, metamorphic rocks, sedimentary rocks and hydrothermal veins. Quartz sand is widely used in industry, electronics, metallurgy and construction, but there are various impurities in its ore, which have an important impact on the quality and application of quartz sand. Therefore, before use, it is necessary to purify and remove impurities in different ways according to the requirements of the purity of quartz sand in the application field. The impurities Al and Fe in quartz are the most difficult elements to remove in the process of quartz sand purification. Al is often present in quartz in the form of mica and feldspar, and Fe is often present in quartz in the form of hematite, magnetite, limonite, etc. At the same time, the two also exist in the quartz lattice in an isomorphic way. When Al and Fe elements exist in the form of minerals such as mica and feldspar, they can be removed by flotation, magnetic separation and other means. However, in this process, only surface impurities can be removed, and deeper impurities cannot be removed. The existing method for removing deep impurities in quartz sand is to roast the quartz sand at a high temperature to transform its crystal structure, and expand and deform in the process, while cracks are generated, and the cracks are deepened during the quenching process to expose the impurities inside the quartz, which are efficiently removed in the subsequent pickling process. However, this method requires a relatively high temperature (1500°C) during the roasting process, and requires a large amount of dye to be roasted, resulting in high purification costs and large fossil energy consumption.

[0003] In order to solve the above problems, those skilled in the art are in urgent need of disclosing a high-pressure pickling method that can efficiently remove impurities inside quartz sand without the need for high-temperature calcination. Summary of the invention

[0004] The object of the present invention is to provide a method for improving the iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid, so as to solve the problems that fluorine-containing waste sulfuric acid is difficult to handle and easily causes environmental pollution, and that pickling of impurities inside quartz sand is difficult and costly.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid, comprising the following steps:

[0007] 1) mixing fluorine-containing waste sulfuric acid, oxalic acid, phosphoric acid, hydrogen peroxide solution, N,N-dimethylformamide, a surfactant and water to obtain a composite high-pressure pickling solution;

[0008] 2) high-pressure pickling of the quartz sand using the composite high-pressure pickling solution in step 1);

[0009] 3) After the high pressure pickling is completed, the quartz sand is washed with water to obtain a quartz sand product;

[0010] The iron content in the quartz sand in step 2) is 400-500 ppm.

[0011] Preferably, the mass concentration of sulfuric acid in the fluorine-containing waste sulfuric acid in step 1) is 70-80%, and the mass concentration of fluoride ions is 2-6%;

[0012] The mass concentration of sulfuric acid in the composite high-pressure pickling solution is 20-30%, and the mass concentration of fluoride ions is 1-2%.

[0013] Preferably, the mass concentration of oxalic acid in the composite high-pressure pickling solution in step 1) is 1 to 3%;

[0014] The mass concentration of phosphoric acid in the composite high-pressure pickling solution is 1-2%;

[0015] The mass concentration of hydrogen peroxide in the composite high-pressure pickling solution is 0.5-0.8%;

[0016] The mass concentration of N,N-dimethylformamide in the composite high-pressure pickling solution is 0.2-0.5%.

[0017] Preferably, the surfactant in step 1) includes one or more of triethanolamine, hexadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride;

[0018] The mass concentration of the surfactant in the composite high-pressure pickling solution is 0.2-0.5%.

[0019] Preferably, the pressure of the high-pressure pickling in step 2) is 0.5 to 1 MPa, and the time of the high-pressure pickling is 2 to 5 hours.

[0020] Preferably, the particle size of the quartz sand in step 2) is 20 to 50 meshes.

[0021] Preferably, the number of water washing in step 3) is 4 to 6 times.

[0022] The present invention has at least the following beneficial effects:

[0023] The present invention adopts industrially produced fluorine-containing waste sulfuric acid as a main component to prepare a composite high-pressure pickling liquid for pickling quartz sand, effectively utilizing fluorine ions and sulfuric acid therein. Fluorine ions can react with quartz sand under acidic conditions, and can penetrate into cracks of quartz sand and expand them in combination with high-pressure pickling, thereby allowing the acid liquid to enter the lattice of quartz sand to remove iron elements existing in the lattice of quartz in an isomorphic manner, thereby improving the whiteness of quartz sand. High-pressure pickling can increase the rate at which fluorine ions enter cracks of quartz sand and shorten the time required for pickling.

[0024] The composite high-pressure pickling solution is prepared from fluorine-containing waste sulfuric acid, wherein the sulfuric acid content can reach 80%, the fluorine content is 2-6%, and the concentration of fluorine ions is low after the sulfuric acid concentration is diluted to a suitable range. The high-pressure pickling effect of quartz sand directly using the diluted solution is poor. The activity of hydrofluoric acid in the solution and the erosion effect on the lattice cracks of quartz sand are improved by adding N,N-dimethylformamide and coordinating with a surfactant, so that the pickling solution can have a better pickling effect at a lower concentration.

[0025] The addition of oxalic acid, phosphoric acid and hydrogen peroxide solution can greatly improve the efficiency of pickling. First, oxalic acid can form a soluble complex with iron ions, making iron easier to dissolve and leach. Phosphoric acid can form soluble phosphates with a variety of metal ions, which can improve the removal efficiency of metal ion impurities. There is also a synergistic effect between oxalic acid and phosphoric acid. The presence of phosphoric acid can promote the complexation of oxalic acid and iron ions. The hydrogen peroxide solution can increase the acidity and oxidation activity of the composite high-pressure pickling solution, oxidize the metal elements in the system into ionic form, and accelerate the pickling rate. DETAILED DESCRIPTION

[0026] The present invention provides a method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid, comprising the following steps:

[0027] 1) mixing fluorine-containing waste sulfuric acid, oxalic acid, phosphoric acid, hydrogen peroxide solution, N,N-dimethylformamide, a surfactant and water to obtain a composite high-pressure pickling solution;

[0028] 2) high-pressure pickling of the quartz sand using the composite high-pressure pickling solution in step 1);

[0029] 3) After the high pressure pickling is completed, the quartz sand is washed with water to obtain a quartz sand product.

[0030] In the present invention, the mass concentration of sulfuric acid in the fluorine-containing waste sulfuric acid in step 1) is 70-80%, and the mass concentration of fluoride ions is 2-6%.

[0031] In the present invention, the mass concentration of sulfuric acid in the composite high-pressure pickling solution is 20-30%, preferably 22-28%, more preferably 24-26%, and more preferably 25%; the mass concentration of fluoride ions is 1-2%, preferably 1.2-1.8%, more preferably 1.4-1.6%, and more preferably 1.5%.

[0032] In the present invention, the mass concentration of oxalic acid in the composite high-pressure pickling solution in step 1) is 1-3%, preferably 1.2-2.8%, more preferably 1.5-2.5%, and more preferably 1.8-2.3%.

[0033] In the present invention, the mass concentration of phosphoric acid in the composite high-pressure pickling solution is 1-2%, preferably 1.3-1.7%, and more preferably 1.5%.

[0034] In the present invention, the mass concentration of hydrogen peroxide in the composite high-pressure pickling solution is 0.5-0.8%, preferably 0.6-0.7%.

[0035] In the present invention, the mass concentration of N,N-dimethylformamide in the composite high-pressure pickling solution is 0.2-0.5%, preferably 0.3-0.4%.

[0036] In the present invention, the surfactant in step 1) includes one or more of triethanolamine, hexadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride.

[0037] In the present invention, the mass concentration of the surfactant in the composite high-pressure pickling solution is 0.2-0.5%, preferably 0.25-0.45%, more preferably 0.3-0.4%, and more preferably 0.35%.

[0038] In the present invention, the pressure of the high-pressure pickling in step 2) is 0.5-1 MPa, preferably 0.6-0.9 MPa, and more preferably 0.7-0.8 MPa; the time of the high-pressure pickling is 2-5 h, preferably 2.5-4.5 h, more preferably 3-4 h, and more preferably 3.5 h.

[0039] In the present invention, the high-pressure pickling method is to place quartz sand in a pickling device, add a composite high-pressure pickling liquid to immerse the quartz sand, introduce nitrogen to increase the pressure inside the pickling device, and the high-pressure pickling liquid flows out through a circulating water pump below the pickling device and then flows into the water inlet above the pickling device for circulating pickling.

[0040] If the pressure of high-pressure pickling is too low, the pickling effect will be poor, and the acid cannot enter the quartz sand lattice, resulting in poor pickling effect; if the pressure of high-pressure pickling is too high, the structure of the quartz sand will be destroyed, resulting in a smaller particle size of the quartz sand, affecting its use.

[0041] In the present invention, the particle size of the quartz sand in step 2) is 20 to 50 meshes, preferably 25 to 40 meshes, and more preferably 30 to 35 meshes.

[0042] In the present invention, the number of times of water washing in step 3) is 4 to 6 times, specifically, water washing is performed until the pH value of the washing liquid is neutral.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and triethanolamine are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 25%, the mass concentration of fluoride ions is 1.6%, the concentration of oxalic acid is 1%, the concentration of phosphoric acid is 2%, the concentration of hydrogen peroxide is 0.5%, the concentration of N,N-dimethylformamide is 0.2%, and the concentration of triethanolamine is 0.3%.

[0046] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.5 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 3 hours.

[0047] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 5 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0048] The iron content of quartz sand before and after pickling was tested. The iron content of quartz sand before pickling was 428ppm, and the iron content of quartz sand after pickling was 48ppm, and the whiteness was 85.

[0049] Example 2

[0050] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and triethanolamine are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 20%, the mass concentration of fluoride ions is 1.25%, the concentration of oxalic acid is 3%, the concentration of phosphoric acid is 1.5%, the concentration of hydrogen peroxide is 0.5%, the concentration of N,N-dimethylformamide is 0.5%, and the concentration of triethanolamine is 0.5%.

[0051] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.6 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 2.5 hours.

[0052] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 6 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0053] The iron content of quartz sand before and after pickling was tested. The iron content of quartz sand before pickling was 424ppm, and the iron content of quartz sand after pickling was 43ppm, and the whiteness was 85.

[0054] Example 3

[0055] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and hexadecyltrimethylammonium chloride are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 30%, the mass concentration of fluoride ions is 1.9%, the concentration of oxalic acid is 2.5%, the concentration of phosphoric acid is 1.4%, the concentration of hydrogen peroxide is 0.6%, the concentration of N,N-dimethylformamide is 0.3%, and the concentration of hexadecyltrimethylammonium chloride is 0.5%.

[0056] (2) placing quartz sand with a particle size of 30 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device reach 1 MPa, and turning on the circulation device in the high-pressure pickling device so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand. The high-pressure pickling is completed after pickling for 2 hours.

[0057] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 5 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0058] The iron content of quartz sand before and after pickling was tested. The iron content of quartz sand before pickling was 433ppm, and the iron content of quartz sand after pickling was 47ppm, and the whiteness was 85.

[0059] Example 4

[0060] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and hexadecyltrimethylammonium chloride are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 28%, the mass concentration of fluoride ions is 1.75%, the concentration of oxalic acid is 1%, the concentration of phosphoric acid is 1%, the concentration of hydrogen peroxide is 0.8%, the concentration of N,N-dimethylformamide is 0.5%, and the concentration of hexadecyltrimethylammonium chloride is 0.3%.

[0061] (2) placing quartz sand with a particle size of 20 to 40 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.6 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 3 hours.

[0062] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 6 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0063] The iron content of quartz sand before and after pickling was tested. The iron content of quartz sand before pickling was 428ppm, and the iron content of quartz sand after pickling was 52ppm, and the whiteness was 85.

[0064] Example 5

[0065] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and dodecyltrimethylammonium chloride are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 20%, the mass concentration of fluoride ions is 1.25%, the concentration of oxalic acid is 2.8%, the concentration of phosphoric acid is 1.3%, the concentration of hydrogen peroxide is 1%, the concentration of N,N-dimethylformamide is 0.4%, and the concentration of dodecyltrimethylammonium chloride is 0.3%.

[0066] (2) placing quartz sand with a particle size of 25 to 45 mesh in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.7 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 4.5 hours.

[0067] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 6 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0068] The iron content of quartz sand before and after pickling was tested. The iron content of quartz sand before pickling was 428ppm, and the iron content of quartz sand after pickling was 50ppm, and the whiteness was 85.

[0069] Comparative Example 1

[0070] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%) and N,N-dimethylformamide are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 25%, the mass concentration of fluoride ions is 1.6%, the concentration of oxalic acid is 1%, the concentration of phosphoric acid is 2%, the concentration of hydrogen peroxide is 0.5%, and the concentration of N,N-dimethylformamide is 0.2%.

[0071] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.5 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 3 hours.

[0072] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 5 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0073] The iron content of the quartz sand before and after pickling was tested. The iron content of the quartz sand before pickling was 428 ppm, and the iron content of the quartz sand after pickling was 94 ppm. The whiteness was 77. Compared with Example 1, no surfactant was added in this comparative example, and the activation effect of hydrofluoric acid was poor. The lattice of the prepared quartz sand product also contained more iron elements.

[0074] Comparative Example 2

[0075] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%) and triethanolamine are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 25%, the mass concentration of fluoride ions is 1.6%, the concentration of oxalic acid is 1%, the concentration of phosphoric acid is 2%, the concentration of hydrogen peroxide is 0.5%, and the concentration of triethanolamine is 0.3%.

[0076] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.5 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 3 hours.

[0077] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 5 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0078] The iron content of the quartz sand before and after pickling was detected. The iron content of the quartz sand before pickling was 428ppm, the iron content of the quartz sand after pickling was 127ppm, and the whiteness was 79. Compared with Example 1, this comparative example did not add N,N-dimethylformamide, and N,N-dimethylformamide had a certain improvement in the penetration ability of hydrofluoric acid. Without adding N,N-dimethylformamide, directly using a pickling solution with a low hydrofluoric acid concentration could not achieve the purpose of removing iron impurities in the quartz sand lattice.

[0079] Comparative Example 3

[0080] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then a hydrogen peroxide solution (30wt%), N,N-dimethylformamide and triethanolamine are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 25%, the mass concentration of fluoride ions is 1.6%, the concentration of hydrogen peroxide is 0.5%, the concentration of N,N-dimethylformamide is 0.2%, and the concentration of triethanolamine is 0.3%.

[0081] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, flushing nitrogen gas to make the pressure in the device 0.5 MPa, turning on the circulation device in the high-pressure pickling device, so that the high-pressure pickling liquid circulates from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand, and completing the high-pressure pickling after pickling for 3 hours.

[0082] (3) Wash the quartz sand after high-pressure acid washing with water. After washing with water for 5 times, use pH test paper to detect that the pH value of the washing solution is neutral, stop washing, and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0083] The iron content of the quartz sand before and after pickling was tested. The iron content of the quartz sand before pickling was 428ppm, the iron content of the quartz sand after pickling was 103ppm, and the whiteness was 80. Compared with Example 1, phosphoric acid and oxalic acid were not added in this comparative example. Although the iron content in the quartz sand after pickling was also significantly reduced, the removal effect was not good. This is because phosphoric acid and oxalic acid can make iron more easily leached and form soluble complexes or salts with iron ions, thereby improving the iron removal effect.

[0084] Comparative Example 4

[0085] (1) Fluorine-containing waste sulfuric acid (sulfuric acid concentration of 80%, fluoride ion concentration of 5%) is diluted with water to obtain a diluent, and then oxalic acid, phosphoric acid, hydrogen peroxide solution (30wt%), N,N-dimethylformamide and triethanolamine are added to obtain a composite high-pressure pickling solution, wherein the concentration of sulfuric acid in the composite high-pressure pickling solution is 25%, the mass concentration of fluoride ions is 1.6%, the concentration of oxalic acid is 1%, the concentration of phosphoric acid is 2%, the concentration of hydrogen peroxide is 0.5%, the concentration of N,N-dimethylformamide is 0.2%, and the concentration of triethanolamine is 0.3%.

[0086] (2) placing quartz sand with a particle size of 25 to 50 meshes in a high-pressure pickling device, injecting the composite high-pressure pickling liquid prepared in step (1) to immerse the quartz sand, and starting the circulation device in the high-pressure pickling device to allow the high-pressure pickling liquid to circulate from the lower part of the pickling device through a water pump to the water inlet at the upper part to perform circulated pickling on the quartz sand. The high-pressure pickling is completed after pickling for 3 hours.

[0087] (3) Wash the acid-washed quartz sand with water. After washing five times, use pH test paper to detect that the pH value of the washing solution is neutral. Stop washing and dry the quartz sand at 80° C. to obtain a quartz sand product.

[0088] The iron content of the quartz sand before and after pickling was tested. The iron content of the quartz sand before pickling was 428ppm, and the iron content of the quartz sand after pickling was 122ppm, and the whiteness was 79. In this comparative example, the pickling equipment was not pressurized with nitrogen during the pickling process, and the fluoride ion had poor intrusion into the quartz sand lattice, and the iron removal efficiency was not high.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid, characterized in that: The following steps are involved: 1) mixing fluorine-containing waste sulfuric acid, oxalic acid, phosphoric acid, hydrogen peroxide solution, N,N-dimethylformamide, a surfactant and water to obtain a composite high-pressure pickling solution; 2) high-pressure pickling of the quartz sand using the composite high-pressure pickling solution in step 1); 3) After the high pressure pickling is completed, the quartz sand is washed with water to obtain a quartz sand product; The iron content in the quartz sand in step 2) is 400-500 ppm.

2. The method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to claim 1, characterized in that: The mass concentration of sulfuric acid in the fluorine-containing waste sulfuric acid in step 1) is 70-80%, and the mass concentration of fluoride ions is 2-6%; The mass concentration of sulfuric acid in the composite high-pressure pickling solution is 20-30%, and the mass concentration of fluoride ions is 1-2%.

3. The method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to claim 2, characterized in that: The mass concentration of oxalic acid in the composite high-pressure pickling solution in step 1) is 1-3%; The mass concentration of phosphoric acid in the composite high-pressure pickling solution is 1-2%; The mass concentration of hydrogen peroxide in the composite high-pressure pickling solution is 0.5-0.8%; The mass concentration of N,N-dimethylformamide in the composite high-pressure pickling solution is 0.2-0.5%.

4. The method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to claim 3, characterized in that: The surfactant in step 1) includes one or more of triethanolamine, hexadecyltrimethylammonium chloride and dodecyltrimethylammonium chloride; The mass concentration of the surfactant in the composite high-pressure pickling solution is 0.2-0.5%.

5. A method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to any one of claims 1 to 4, characterized in that: The pressure of the high-pressure pickling in step 2) is 0.5-1 MPa, and the time of the high-pressure pickling is 2-5 hours.

6. The method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to claim 5, characterized in that: The particle size of the quartz sand in step 2) is 20 to 50 meshes.

7. The method for improving iron removal efficiency by high-pressure pickling of quartz sand using fluorine-containing waste sulfuric acid according to claim 6, characterized in that: The number of times of washing with water in step 3) is 4 to 6 times.

Citation Information

Patent Citations

  • Ultrapure quartz sand and purification process thereof

    CN109081352A

  • Process method for preparing high-purity quartz sand by taking cobblestones as raw materials

    CN114195159A

  • Pickling purification method for quartz sand

    CN114455590A

  • Process for preparing ultra-high-purity quartz powder from mud-containing quartzite and comprehensively utilizing ultra-high-purity quartz powder

    CN115178363A

  • Method for preparing high-purity quartz sand through ultrasonic-assisted pickling

    CN117945408A

Cited By

  • Quartz sand purification method

    CN121342038A